FAKTOR INTERNAL DAN EKSTERNAL YANG MEMENGARUHI KREDIT MACET DI BANK UMUM KONVENSIONAL - Nisa, Khanifatun; Pramono, Nugroho Heri (Jurnal Riset Keuangan dan Akuntansi, 2024)
This study aims to determine the effect of internal and external bank factors on Non Performing Loan at conventional commercial banks. This research data is secondary data sourced from annual reports that have been published on the Indonesia Stock Exchange (IDX). The population in this study includes conventional commercial banks listed on the Indonesia Stock Exchange (IDX) in 2020 – 2022. Sampling using purposive sampling method so that 42 banks were obtained. The data analysis method in this research is multiple linear regression analysis using the help of SPSS version 25 software. Based on the results of the study, it shows that CAR and Gross Domestic Product have a negative effect on NPLs. While LAR, company size, and interest rates have no effect on NPLs. Keywords: non performing loan; internal factors; and external factors